Identità narrative e progettazione dell'"opera" - Giuseppe Annacontini (Firenze University Press, 2017)
The essay highlights on relationship between educational planning, the concept of "opera" and narration. Therefore the essay considers first of all the pedagogy of Giovanni Maria Bertin and his "Pedagogic Problematicism", a theory that promotes an intentionality of pedagogy that surpasses dogmatic positions. In this direction, central is the role played by the relationship between the subject and the world, a link that, in this essay, refers to the ways thanks to which these two complement poles interact each other determining "productive events" of meaning The outcome is an anti-dogmatic approach that prevents skeptic results in order to produce "opera". However, this "opera" intended as a relationship between ground and world built on the recognition of "a thousand plans" beneath what we can "call life" and make "life story". Producing "opera" means knowing how to narrate oneself and decide to narrate means "cultivating and caring for own subjectivity creatively oriented". Indeed, an education which makes subjects competent in narrate oneself produces new and open "frames" to "begin to govern" story and life.